Designing Educational Media about the Inner Child for Adolescents Using Digital Illustrated Books - Absyir Abdul Wahhab; Damar Rangga Putra; Bayyinah Nurrul Haq (IMAGIONARY, 2023)
Mental health issues are getting more attention since more people open themselves on social media related to psychological problems they experience. The problems they face are likely past traumas that carry over into adulthood. This paper is about designing an illustrated e-book that discusses the inner child or "little child" that exists in every human being. The design method used is The Design Method introduced by Eric Karjoluoto. The design process consists of four stages, namely discovery, planning, creativity, and application. Concept development using the 5W+1H technique. The result of the design is a concise, lightweight format e-book, consisting of 26 pages. The book outlines the Prologue – Characteristics of a wounded Inner child – Transition – How to heal a wounded Inner child – Conclusion – Transition – hook. The arrangement of book content aims to provide knowledge about what the inner child is, and what makes the inner child.